Effects of Class II Malocclusion Therapy with Four First Premolars Extraction on Third Molar Eruption - Hatice Gökalp (Galenos Yayinevi, 2006)
The cause of third molar impaction is generally attributed to the insufficiency of the eruption space. The factors causing third molar impaction can be summarized as; heredity, race and familial influences. It has been reported in many studies that orthodontic treatment with extraction decreases the incidence of the third molar impaction due to maintenance of the space needed. The objectives of the present investigation are to evaluate the changes in maxillary and mandibular third molar angulations during active orthodontic treatment with extraction of premolars in Class II malocclusions, and to compare changes of upper and lower third molars' angulations occurred with the change at upper and lower incisors and molars positions.